Small RNA Profiling of Susceptible and Resistant Ty-1 Encoding Tomato Plants Upon Tomato Yellow Leaf Curl Virus Infection - Voorburg, Corien M.; Bai, Yuling; Kormelink, Richard (Frontiers in plant science, 2021)
Ty-1 presents an atypical dominant resistance gene that codes for an RNA-dependent RNA polymerase (RDR) of the gamma class and confers resistance to tomato yellow leaf curl virus (TYLCV) and other geminiviruses. Tomato lines bearing Ty-1 not only produce relatively higher amounts of viral small interfering (vsi)RNAs, but viral DNA also exhibits a higher amount of cytosine methylation. Whether Ty-1 specifically enhances posttranscriptional gene silencing (PTGS), leading to a degradation of RNA target molecules and primarily relying on 21–22 nucleotides (nts) siRNAs, and/or transcriptional gene silencing (TGS), leading to the methylation of cytosines within DNA target sequences and relying on 24-nts siRNAs, was unknown. In this study, small RNAs were isolated from systemically TYLCV-infected leaves of Ty-1 encoding tomato plants and susceptible tomato Moneymaker (MM) and sequence analyzed. While in susceptible tomato plants vsiRNAs of the 21-nt size class were predominant, their amount was drastically reduced in tomato containing Ty-1 . The latter, instead, revealed elevated levels of vsiRNAs of the 22- and 24-nt size classes. In addition, the genomic distribution profiles of the vsiRNAs were changed in Ty-1 plants compared with those from susceptible MM. In MM three clear hotspots were seen, but these were less pronounced in Ty-1 plants, likely due to enhanced transitive silencing to neighboring viral genomic sequences. The largest increase in the amount of vsiRNAs was observed in the intergenic region and the V1 viral gene. The results suggest that Ty-1 enhances an antiviral TGS response. Whether the elevated levels of 22 nts vsiRNAs contribute to an enhanced PTGS response or an additional TGS response involving a noncanonical pathway of RNA dependent DNA methylation remains to be investigated.